STRUCTURAL DESIGN OF THE PILE SLAB BRIDGE IN DAMIT HULU - Mario Paska Wahyudi Tanujaya; Gawit Hidayat; Humaira Afrila; Markawie Markawie (CERUCUK, 2026)
A bridge is a structure built to connect two areas separated by obstacles such as rivers, ravines, or bodies of water. In Damit Hulu Village, there is an area that frequently becomes flooded during the rainy season, hindering the transportation activities of the local community. To address this issue, a bridge was designed to facilitate the movement of residents in the area. The design process adheres to national standards, namely SNI 1725:2016, SNI 2833:2016, and SNI 2847:2019, and is supported by structural analysis software. The planned bridge is a pile slab type with a length of 40 meters and a width of 6 meters. Based on the design results, the floor slab thickness is 0.3 meters, and the pile cap dimensions are 0.8 meters in width, 6 meters in length, and 0.5 meters in height. All structural components have been verified to meet the technical standards in accordance with applicable regulations. Keywords: Damit Hulu, Pile Slab, Pile cap, Floor Slab